Alysicarpus hamosus var. trifoliolatus (Fabaceae) a new variety from Deccan plateau of India. - Chavan, Shantanu; Taur, Ruplali; Dhabe, Arvind (Plantae Scientia, 2025)
A new variety, Alysicarpus hamosus var. trifoliolatus, has been identified and described from the Dr. Babasaheb Ambedkar Marathwada University Campus, Chhatrapati Sambhajinagar, and other localities in Maharashtra. This variety belongs to the genus Alysicarpus in the family Fabaceae and is distinct from the closely related Alysicarpus hamosus. Morphologically, Alysicarpus. hamosus var. trifoliolatus is similar to Alysicarpus hamosus but can be distinguished by several key characteristics: it features trifoliolate leaflets, unique leaflet shapes and sizes, distinct petal color and morphology, and specific pod structures. Additionally, the variety has non-mottled seeds and a distinctive seed surface pattern. The new variety is described and illustrated, providing detailed morphological comparisons with Alysicarpus hamosus and enhancing the understanding of its taxonomic placement within the genus. This description contributes to the botanical knowledge of the region and aids in the identification and classification of the species.